Urban Climate Politics in Emerging Economies: A Multi-Level Governance Perspective. (November 2022) - Stehle, Fee; Hickmann, Thomas; Lederer, Markus; Höhne, Chris
Several scholars have pointed to the increasing salience of cities in the global endeavour to reduce dangerous climate change to 1.5°C. However, we still lack systematic comparative analyses on how urban climate initiatives evolve in different political-administrative systems of countries in the global South and what role transnational city networks play in that context. This question is specifically important with regard to the role of cities in contributing to reaching the targets of the Paris Agreement. Against this backdrop, this article explores the vertical and horizontal integration of cities' climate actions in the multi-level climate governance landscapes in Brazil, India, Indonesia and South Africa. We contend that while transnational city networks provide significant support to cities in some cases, their tools and practices can only reach their full potential where they encounter committed local administrations and when they are not constrained by domestic political-administrative and economic factors.